The high road [compact disc] - Brown, Kane, 1993- (Sony Music Nashville, 2025)
ACM Award winning artist Kane Brown is back with the follow up to his hit 2022 album Different Man. Among the tracks are the hits Miles On It and Fiddle in the Band.